Provider attitudes towards a brief behavioral intervention for sexual health in Moldova - Rob Stephenson; Galina Lesco; Viorel Babii; Andrei Luchian; Nataliia Bakunina; Ana Sofia De Vasconcelos; Karel Blondeel; Carlos F. Cáceres; Renée A. Pitter; Nicholas Metheny; Tamar Goldenberg; James Kiarie; et al. (BMC, 2021)
Abstract Background Brief behavioral interventions are seen as an efficient way to improve knowledge, change behavior, and reduce provider stigma regarding sexual health. When grounded in evidence-based behavioral change techniques and delivered using Brief Sexuality-related Communication (BSC) tools, brief behavioral interventions can address client-driven sexual health goals in a single session with their provider. Evidence for the efficacy of brief interventions for creating gains in sexual health comes largely from resource rich settings, and there is a lack of knowledge of how brief interventions can be implemented in the more resource constrained environments of low- and middle-income countries. As a first step in developing a brief intervention to address sexual health issues in Moldova, this paper reports on qualitative data collected from Moldovan providers to understand their attitudes, willingness and perceived barriers to the brief intervention and its implementation. Methods Thirty-nine in-depth interviews (IDI) were conducted between February and March 2020, with health providers recruited from three primary health care institutions, two Youth Friendly Health Centers and counselors from three NGOs who work with key populations in Moldova, including health centers selected from two cites - the capital city, Chisinau and from the Comrat Region. The IDI addressed four domains of provider attitudes: 1) attitudes towards the intervention; 2) willingness and motivation to implement the intervention; 3) logistics of providing the intervention and 4) ability to implement the intervention. A coding analysis approach was applied to all interview transcripts. Results Providers largely reported being willing to be trained in and implement the brief intervention. Willingness to implement the intervention stemmed from two perceptions: that it would improve the ability of providers to talk with their clients about sex, and that vulnerable groups would benefit from these conversations. However, while there were generally positive attitudes towards the intervention, providers consistently reported structural barriers to their perceived ability to implement the intervention. Conclusions While providers reported high levels of initial acceptance of a brief behavioral intervention, care is needed to ensure that brief interventions, and the training of providers on brief interventions, incorporate cultural attitudes and norms around sex, particularly in highly patriarchal settings, and provide opportunities for providers to practice the intervention in ways that address their assumptions and implicit biases.